Characterization of starfruit-like PbWO4 microstructured clusters synthesized by a solution route - Phuruangrat A. (2017)
Starfruit-like PbWO 4 microstructured clusters were synthesized by a solution route of Pb(NO 3 ) 2 and Na 2 WO 4 in ethylene glycol. The product was characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, Fourier transform infrared spectroscopy and photoluminescence spectroscopy. In this research, tetragonal PbWO 4 microstructured clusters in the shape of starfruits were detected. PL spectrum excited by 286 nm wavelength was divided into three individual components with the maximum blue emission at 390 nm (40.79%), 424 nm (30.30%) and green emission at 472 nm (28.91%).